Nordic Walking or Traditional Walking in Patients With Intermittent Claudication: A Critical Review - Upeniece, Irēna; Šmite, Daina; Arnis, Voldemārs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Regular exercises can improve walking distance and reduce physical impairment in patients with intermittent claudication. The objective of the research is to summarise and analyse the existing proof about the comparative effectiveness of Nordic walking and traditional walking in the improvement of health indicators in patients with intermittent claudication. Methods: The following online databases were used as sources for data collection: Ebsco, Sience Direct, Clinical Key, ProQuest, Scopus. The selection of works of research was performed on the basis of key words “Nordic walking”, “intermittent claudication”, “walking with poles”, “Nordic walking and walking and intermittent claudication” and the year of publishing (that is, from 2005 till 2015). Inclusion criteria met four works of research that were included in the critical analysis. Results and conclusions: There is no proof about the superiority of the Nordic walking programme over traditional walking (and there exist indications about the superiority of the traditional walking programme) in the improvement of helath indicators, but patients with intermittent claudication feel less discomfort during Nordic walking and they can cover a longer distance by using poles.